Kaskade : Afstudeerprojecten 2006 Koninklijke Academie voor Schone Kunsten Antwerpen Conservatie/restauratie. - Ubben, Eric; Van der Star, Carolien; Koninklijke Academie voor Schone Kunsten, Antwerpen (Antwerpen : Koninklijke Academie voor Schone Kunsten Antwerpen, 2006)
Allegaert, Nele ; Bastyns, sofie ; Cauberghs, Sabine ; Costimao, Tim ; Cuvelier, Liesbet ; Daneels, Ellen ; De Block, Marjan ; De Clerck, Evelyne ; De Saedeleer, Greet ; den Brok, Jantine ; Detemmerman, Zofia ; Fonteyne, Leslie Roxanne ; et al.
Koninklijke Academie voor Schone Kunsten Antwerpen, Antwerpen, Conservatie/restauratie, juni en juli 2006
kunstcatalogus